Catch-and-release angling as a management tool for freshwater fish conservation in India. Issue 2 (10th November 2014) - Gupta, Nishikant; Nautiyal, Prakash; Borgohain, Atul; Sivakumar, K.; Mathur, Vinod B.; Chadwick, Michael A.
Abstract: Mahseer are popularly regarded by anglers as the king of freshwater fishes, and are valued across the Himalayan and South-east Asian regions. In India, mahseer are important game fish. Mahseer populations and their habitats face a range of anthropogenic threats, however, including unregulated fishing and habitat fragmentation as a result of hydro-development projects. Catch-and-release angling for mahseer attracts both national and international anglers and could provide information about rivers while generating revenue for regional economies. In this context, we evaluated catch-and-release angling records from rivers that flow within two Indian reserves (the Ramganga and Jia Bharali Rivers in Corbett and Nameri Tiger Reserves, respectively). Golden mahseer Tor putitora in the Ramganga and golden and chocolate mahseer Neolissochilus hexagonolepis in the Jia Bharali were the most frequently caught fish species. Catch data suggested these game fish populations are probably not negatively affected by angling activities. Interviews with stakeholders highlighted support for catch-and-release angling, mainly because of its perceived economic benefits. The data obtained in this research could potentially assist with both fish conservation and the protection of associated aquatic ecosystems.